A systematic review and cost analysis of repeat colonoscopies due to inadequate bowel cleansing in five European countries. (2nd November 2019) - Murphy, Daniel; Jenks, Michelle; McCool, Rachael; Wood, Hannah; Young, Victoria; Amlani, Bharat
ABSTRACT: Background : Colonoscopies are carried out for a range of reasons including for the detection of colon cancer and investigation of abdominal and bowel related symptoms. Inadequate preparation can increase the burden of repeat procedures. Methods : A systematic review aimed to identify the rate of repeat colonoscopies due to inadequate bowel preparation in France, Germany, Italy, Spain and the United Kingdom. The information obtained populated a decision analytic model to estimate the cost implications of inadequate bowel cleansing in the same five countries. The model explored scenarios by comparing one and two-litre polyethylene glycol-based bowel preparation. Results : The systematic review identified 14 eligible studies reporting on the proportion of patients with inadequate bowel cleansing indicated for a repeat procedure. Data were available for Italy (27.5%-35.9%), Spain (63%) and the UK (24.5%) only. The decision analytic model demonstrates that improving the proportion of adequate bowel cleansing at first colonoscopy is likely to generate cost savings. Conclusions : Based on the available evidence, increasing the proportion of people who have adequate bowel cleansing at index colonoscopy will likely have financial benefits in Italy, Spain and the UK. A paucity of data, for France and Germany, limits the robustness of conclusions in these countries.